Pembuatan Kalsium Karbonat Dari Batu Kapur Bukit Tui Kota Padang Panjang - Rusdi Rusdi; Metalia Maryesri; Zulharmitta Zulharmitta (STIFARM Padang, 2013)
A Research has been done about preparing calcium carbonat from limestone of Bukit Tui Kota Padang Panjang. The sample as much as 20 g was dissolved in HCl 6 M, the resulting filtrate reacted with NH4OH 6 M to the pH of 8 and reacted with (NH4)2CO3 6 M until no more precipitate was was formed. The precipitate was separated and dried in oven for 4 hours at 105º C. Ten g of the dried precipitate was determined complexometrically using EDTA as complexson and murexide as indicator. It was found that the limestone at Bukit Tui Kota Padang Panjang contained 67.2 % w/w calcium carbonate in comparison to reference compound 103.99 % w/w.